The Identification of Stereotypes in the Artistic Text: (On the Basis of Ukrainian, Polish and British Realist Prose) - Burak, Vira (JOURNAL OF ADVANCES IN LINGUISTICS, 2018)
Stereotypes are an extremely complex object of research. Mental construction cannot be static. Old stereotypes slowly change, new ones appear and with the help of various codes (linguistic, cultural, literary) the author encrypts all of this into the artistic text. Besides the existence of linguistically expressed but not linguistically fixed stereotypes in artistic texts, stable stereotypes undergo different modifications of sense and verbalization forms. The ultimate goal of the research is to identify the factors which determine the form and the meaning of stereotypes verbalizers; to carry out a functional differentiation of linguistic signs that refer to these conventional referents in Ukrainian, Polish and British realist prose. Stabilized stereotypes are fixed by nominations of different structural and semantic complexity. Within the limits of the semantic structure of a nomination there is a hierarchy of semantic features: their typicality, frequency of functioning and, hence - stereotypicality - decreases from the center towards the periphery. In the core zone, semantics of a stereotype coincides with the semantics of a prototype. Stereotypes with different degree of conventionality and communicative relevance are explicated in artistic texts with the help of structurally different nominative and communicative units.